Upaya Meningkatkan Keterampilan Senam Lantai Guling Depan Melalui Pembelajaran Berdiferensiasi Pada Peserta Didik Di MTS Arifah Gowa - Yasin, Niswar Asriwandi; Ihsan, Andi; Hudain, Muh. Adnan; Hasmyati, Hasmyati; Adil, Ahmad (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
The research aims to improve floor rolling exercise skills through differentiated learning for class VII students. 1 MTs Arifah Gowa. This research is classroom action research (PTK). This research was carried out in two cycles, with each cycle consisting of planning, implementing actions, observing and reflecting. The research subjects were class VII students. I MTs Arifah Gowa, totaling 28 students. Data collection techniques are tests and observations. Data analysis uses qualitative descriptive techniques using percentage techniques. The results of the data analysis can be presented as follows: the learning results of the front roll floor exercise for class VII students. I MTs Arifah Gowa in Cycle I of 28 students reached 43% or as many as 12 students had entered the criteria for completion and 57% or as many as 16 students had criteria for not completing. In Cycle II it increased to 82% or as many as 22 students entered the criteria for completing, while as many as 18% or as many as 6 students did not complete the criteria. From the results of the data analysis above, it can be concluded that through differentiated learning it can improve learning outcomes for front roll floor exercise in class VII students. I MTs Arifah Gowa